Sistem "full pre trial disclosure" dalam penegakan asas peradilan sederhana, cepat, dan biaya ringan - Wika Yudha Shanty (Jurnal Cakrawala Hukum, 2020)
Legal principles as basic norms are described as the basis / general guidelines forpositive law / applicable law. One of the legal principle problems that will be discussedby researchers in this research is about the application of principles that arenot in accordance with the reality that occurs in court. There are too many formalitiesthat are difficult to understand, and the rules are not clear, which allows for multiple interpretations and results in fear of proceeding in court. Too many formalitiesare an obstacle to the running of the courts. In this case the problem is notonly in the examination at trial, but also in the settlement of the examination reportat the trial until the signing of the decision by the judge and its implementation. Itoften happens that a case is delayed for years because the witnesses do not come, orthe parties in turn do not come or decide to withdraw from the case. In fact, there areseveral cases that were continued by their heirs. Meanwhile, in terms of costs incourt, the high court costs will cause interested parties to think again and againabout filing a claim to court. Based on this, it can be concluded that the speed withwhich the trial runs will increase the court’s authority and increase public confidencein the court.